vault backup: 2025-02-16 18:32:21
This commit is contained in:
parent
83569114c2
commit
341c388d37
@ -133,10 +133,11 @@ $$ \dfrac{d}{dx} \csc x = -\csc x \cot x $$
|
||||
## Cotangent
|
||||
$$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
||||
|
||||
# Implicit Differentiation\
|
||||
- $\dfrac{d}{dx} * x^2 = \dfrac{d(x^2)}{dx}$, or, the derivative of $x^2$ with respect to x
|
||||
- $\dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one
|
||||
-
|
||||
# Implicit Differentiation
|
||||
- There's a reason differentials are written like a fraction
|
||||
- $\dfrac{d}{dx} x^2 = \dfrac{d(x^2)}{dx}$, or, "the derivative of $x^2$ with respect to $x$"
|
||||
- $\dfrac{d}{dx} x = \dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one
|
||||
- $\dfrac{d}{dx} y = \dfrac{{dy}{dx} = y'$
|
||||
# Examples
|
||||
|
||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||
|
Loading…
x
Reference in New Issue
Block a user